2001
DOI: 10.1002/chin.200105212
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phenolic Constituents of Licorice. Part 8. Structures of Glicophenone and Glicoisoflavanone, and Effects of Licorice Phenolics on Methicillin‐Resistant Staphylococcus aureus.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A recent investigation found that some polyphenolic compounds isolated from tea and some medicinal plants are effective against MRSA. [1][2][3][4][5][6][7][8] We found that not only plant phenolics, but also a polyphenolic compound produced from a natural polyphenol, showed a potent inhibitory effect on the antibiotic resistance of MRSA: 9) Theasinensin A, an oxidation product from (À)-epigallocatechin gallate (EGCG), formed upon incubation under very mild conditions and lowered the minimum inhibitory concentration (MIC) values of oxacillin and several other antibiotics against MRSA.…”
Section: Polyphenolic Constituent Structures Of Zanthoxylum Piperitummentioning
confidence: 99%
“…A recent investigation found that some polyphenolic compounds isolated from tea and some medicinal plants are effective against MRSA. [1][2][3][4][5][6][7][8] We found that not only plant phenolics, but also a polyphenolic compound produced from a natural polyphenol, showed a potent inhibitory effect on the antibiotic resistance of MRSA: 9) Theasinensin A, an oxidation product from (À)-epigallocatechin gallate (EGCG), formed upon incubation under very mild conditions and lowered the minimum inhibitory concentration (MIC) values of oxacillin and several other antibiotics against MRSA.…”
Section: Polyphenolic Constituent Structures Of Zanthoxylum Piperitummentioning
confidence: 99%
“…Similarly, blank is prepared; respective solvents were used instead of the extracts. The total antioxidant capacity in aqueous extracts of different pH was calculated from the standard curve and expressed as mg AAE/g (milligram ascorbic acid equivalent per gram).Antioxidant ActivityAntioxidant activity was estimated by DPPH free radical scavenging activity method in aqueous extracts of Mulhatti aerial parts of different pH, namely 2, 4, 7 and 9[12]. The aqueous extract was taken and dried completely and the dry mass was recorded.…”
mentioning
confidence: 99%